Chinese Expert Consensus on Iodine125 Seed Implantation for Recurrent Cervical Cancer in 2021 - Jiang, Ping; Zou, Lijuan; Wei, Lichun; Cheng, Guanghui; Sun, Baosheng; Zhang, Fuquan; Wang, Ruoyu; Wang, Tiejun; Qu, Ang; Yuan, Xiangkun; Qiu, Bin; Wei, Shuhua; et al. (Frontiers in Oncology, 2021)
Treatment modality for recurrent cervical cancer (rCC) is limited and the prognosis of these patients is poor. Seed implantation could be an important component of rCC management in the context of dose boost or salvage therapy after surgery or radiotherapy, which is characterized by minimally invasive, high local dose, and rapidly does fall sparing normal tissue. For patients with good performance status and lateral pelvic wall recurrence with an available puncture path, seed implantation was recommended, as well as for selected central pelvic recurrence and extra-pelvic recurrence. The combination of brachytherapy treatment planning system and CT guidance was needed and three-dimensional printing templates could greatly improve the accuracy, efficiency, and quality of seed implantation, to achieve a potential ablative effect and provide an efficient treatment for rCC. However, the recommendations of seed implantation were mainly based on retrospective articles and lack high-quality evidence, and multicenter prospective randomized studies are needed. In this consensus on Iodine125 seed implantation for rCC, indication selection, technical process and requirements, dosimetry criteria, radiation protection, combined systemic therapy, and outcomes of seed implantation for rCC are discussed.